Coupled Production of Steel and Chemicals. Issue 11 (20th August 2018) - Bender, Michael; Roussiere, Thomas; Schelling, Heiner; Schuster, Sabine; Schwab, Ekkehard
Abstract: Within Carbon2Chem® the presented subproject focused on oxymethylene ethers (OME) as possible diesel fuel components. Six different scenarios for CO2 emission reduction in steel mills were calculated, in four of which methanol is generated as an OME intermediate from steel mill gases. Potential synergies in raw material and energy streams of the coupled processes were identified. Shared process streams and equipment could lead to savings in capital and operational expenditure. CO2 reduction volumes and avoidance costs were calculated for the six scenarios. If coupled with methanol production, natural gas‐based direct reduced iron processes offer the chance for quantitative CO2 emission reduction at the lowest CO2 avoidance costs. Energy required for this process could be co‐fed, e.g., as renewable electricity. Abstract : In a Carbon2Chem® subproject the production of oxymethylene ethers via methanol from steel mill gases was investigated. If coupled with methanol production, natural gas‐based direct reduced iron processes offer the chance for quantitative CO2 emission reduction in steel mills at the lowest CO2 avoidance costs. The required energy could be supplied as renewable electricity.